2022
DOI: 10.1186/s12929-022-00799-x
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenic effects of particulate matter on neurodegeneration: a review

Abstract: The increasing amount of particulate matter (PM) in the ambient air is a pressing public health issue globally. Epidemiological studies involving data from millions of patients or volunteers have associated PM with increased risk of dementia and Alzheimer’s disease in the elderly and cognitive dysfunction and neurodegenerative pathology across all age groups, suggesting that PM may be a risk factor for neurodegenerative diseases. Neurodegenerative diseases affect an increasing population in this aging society,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 113 publications
0
21
0
1
Order By: Relevance
“…Previous reviews have preliminary illustrated relevant mechanisms from the perspective of PM-related cell death patterns or the perspective of certain diseases or systems, pointing out that oxidative stress, inflammation, apoptosis, autophagy and DNA damage are the main mechanisms leading to the adverse effects of PM [12,[22][23][24]. In vitro and in vivo studies have shown that PM 2.5 causes oxidative stress through the induction of reactive oxygen species (ROS), which leads to dysregulation of calcium homeostasis and cytotoxicity [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews have preliminary illustrated relevant mechanisms from the perspective of PM-related cell death patterns or the perspective of certain diseases or systems, pointing out that oxidative stress, inflammation, apoptosis, autophagy and DNA damage are the main mechanisms leading to the adverse effects of PM [12,[22][23][24]. In vitro and in vivo studies have shown that PM 2.5 causes oxidative stress through the induction of reactive oxygen species (ROS), which leads to dysregulation of calcium homeostasis and cytotoxicity [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…PM invades brain tissue via direct transmission through the nasal epithelium and olfactory receptor neurons [ 7 ] or blood circulation. [ 8 ] A previous post‐mortem study showed that magnetic nanoparticles were observed in the brain tissues obtained from all 38 cases, [ 9 ] indicating that PM had penetrated the brain. Individuals exposed to PM show several notable features, such as impaired brain development, cognitive deficits, inflammation in the blood–brain barrier (BBB), and the accumulation of neurotoxic protein aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals exposed to PM show several notable features, such as impaired brain development, cognitive deficits, inflammation in the blood-brain barrier (BBB), and the accumulation of neurotoxic protein aggregates. [8] The exposure of brain tissue to PM has a negative effect on the central nervous system (CNS) and can cause dementia, [10] stroke, [11] depression, [12] and schizophrenia. [13] To investigate PM toxicity, 2D culture systems and animal models have been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Harmful systemic health effects of PM 10 or PM 2.5 are often attributable to the UFP fraction. According to recent works [ 181 , 182 ], exposure to combustion-generated ultrafine particles and engineered nanoparticles can also be linked to neurodegenerative diseases documented in young, urbanised residents of polluted cities.…”
Section: Scientific Backgroundmentioning
confidence: 99%